Effect of Anredera cordifolia (Binahong) Extract on C-Peptide Levels in Streptozotocin-Induced Diabetic Sprague–Dawley Rats - Salsabila Hafsah Hasanah; Nurlaely Mida Rachmawati; Luluk Hermawati; Ervina Julien Sitanggang (Stem Cell and Cancer Research (SCCR), 2026)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia resulting from impaired insulin secretion, impaired insulin action, or both, and remains a major global health concern. Anredera cordifolia (binahong) is a medicinal plant commonly used in traditional medicine and is known to contain bioactive compounds such as saponins, alkaloids, polyphenols, and flavonoids, which have been suggested to possess antidiabetic and antioxidant properties. Objective: This study aimed to evaluate the effect of Anredera cordifolia leaf extract on C-peptide levels as a marker of endogenous insulin secretion in streptozotocin (STZ)-induced diabetic rats. Results: A total of 24 male Sprague–Dawley rats were randomly divided into three groups: negative control (without STZ induction or treatment), positive control (STZ-induced), and treatment group (STZ-induced rats receiving Anredera cordifolia leaf extract at a dose of 100 mg/kg body weight/day). Diabetes was induced by a single intraperitoneal injection of STZ at a dose of 50 mg/kg body weight, and rats with random blood glucose levels ≥200 mg/dL were included in the diabetic groups. The extract was administered orally for 14 days. At the end of the intervention period, blood samples were collected, and plasma C-peptide levels were measured using an enzyme-linked immunosorbent assay (ELISA) and analyzed with a microplate reader. Statistical analysis using the Kruskal–Wallis test demonstrated no significant difference in mean C-peptide levels among the three groups (p = 0.132). Conclusion: These findings indicate that administration of Anredera cordifolia leaf extract at the tested dose and duration did not significantly affect C-peptide levels in STZ-induced diabetic Sprague–Dawley rats, suggesting that its potential antihyperglycemic effects may not be associated with measurable improvement in pancreatic β-cell secretory function under these experimental conditions.